Transfer and business taxation made easy - Ballada, Susan (Sampaloc, Manila : DomDane Publisher, 2014)
This book can maximize learning and comprehension at the least possible time and effort. This text is annually updated and fine-tuned; therefore, the users can rely on this text for their strategic academic preparations.
Part One Transfer Taxes -- Introduction 1 -- Estate Taxes -- Basic Concepts of Succession 4 -- Gross Estate 25 -- Deductions from Gross Estate 55 -- Net Taxable Estate and Estate Tax 89 -- Net Estate and Estate Tax: Unmarried Decendent 91 -- Net Estate and Estate Tax: Conjugal Partnership 101 -- Net Estate and Estate Tax: Absolute Community 129 <br Tax Credit for Foreign Estate Tax 141 -- Administrative Provisions 153 -- Donor's Taxes -- Basic Concepts of Donation 163 -- Gross Gift 171 -- Exemptions from Gross Gift 177 -- Net Taxable Gift and Donor's Tax 183 -- Part Two Business Taxes -- Nature and Concept of Business Taxes 201 -- Value-Added Tax -- VAT on Sale of Goods or Property 203 -- VAT on Sale of Service and Use or Lease of Property 225 -- VAT on Importation of Goods 249 -- Output and Input Taces 251 -- VAT Exempt Transactions 263 -- Compliance Requirements 281 -- Withholding and Remittance of VAT 287 -- Percentage Taxes -- Rates and Bases of Percentage Tax 317 -- Withholding of Percentage Taxes 335 -- Penalties and Remedies 343 -- Ethical Considerations 350 -- Local Direct Taxes 353 -- Student Tracking System
Includes bibliographical references.
Keywords: BUSINESS TAX